POT LUCK: THE UNIQUENESS OF 1USM OPEN HOUSE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – The concept of "Pot Luck" was evident and proven to be successful in the recent 1USM Aidilfitri celebrations, where various PTJs (Schools and Centres) in the university contributed different types of food items to be shared together, in an effort to create a sense of togetherness during the event.